Pengaruh Lingkungan Kerja Terhadap Motivasi Peserta Magang Msib 7 Di Ruang Belajar Aqil - Sasikaraya, Alfentira Mega; Nafi'ah, Binti Azizatun (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
Magang dan Studi Independen Bersertifikat (MSIB) is a government program created by the Ministry of Education and Culture and was first held in 2021 with the aim of providing practical-based experience to students and producing graduates who are ready to work. This research examines the influence of the work environment on the motivation of MSIB Batch 7 interns at Ruang Belajar Aqil (RBA), a non-profit institution in Malang City that focuses on quality education and community empowerment. The research method used was qualitative with in-depth interviews with MSIB Batch 7 interns in Assistant positions. The research results show that the physical (facilities, cleanliness) and non-physical work environment (relationships between individuals, communication, appreciation) have a significant influence on the motivation of interns. Interns who have high motivation will contribute and produce optimal performance. The causes of decreased motivation of interns are excessive workload and lack of effective communication. This research emphasizes the importance of managing a supportive work environment to increase the motivation and performance of interns.